Analysis of Sources of Use of Working Capital Period 2011–2020 - Irsan, Muhammad (AIBPM Publisher, 2023)
The purpose of this research is to analyze how the source and use of working capital PT. Pelabuhan Indonesia 1 Medan (Persero) and conduct an analysis of the problems that arise as well as the impact of a decrease or increase in the use of working capital sources of PT. Pelabuhan Indonesia 1 Medan (Persero) which experienced fluctuating conditions (up and down) working capital was not followed by income. The approach used in this study was a descriptive approach, namely collecting data, clarifying data, explaining data, and analyzing data. In this study the authors calculate the net working capital, sources and uses of working capital by using the financial statements in the form of a balance sheet and profit and loss. The descriptive data used is documentation data collection techniques.